(untitled) (Italian Journal of Public Health, 2012)
According to the WHO-European region Tallin-Charter, Stewardship (S) is on the health agenda of many European countries and in particular of those involved in the devolution of powers, as is the case of Italy. Many observers agree that, in such cases, both the configuration and the application of state authority in the health sector should be realigned so as to achieve desired policy objectives.We present an experience of what could be meant by S in practice, applied to the field of planning preventive interventions.The Italian National Preventive Plan 2010-2012 is a comprehensive Plan dealing with many areas of prevention. For all these areas, the main health objectives, the specific regional goals and the intervention - called “central" actions- that the Ministry of Health (MoH) is in charge of carrying out in order to support regional preventive programs, are stated in this Plan. In order to carry out its task, the MoH has referred to the model of stewardship and has reconsidered its role. Therefore, the MoH has matched the sub-functions of S according to the model outlined by Travis et al, and the prior actions that have been proposed by local and national governments, as the main aspects of how to deal with the governance of prevention. Overall, we experienced that the S framework is a suitable and helpful tool to tackle what the challenge of national planning, in the scenario of devolution, is. In doing so, we have learnt some practical lessons about the running of the system and about how to plan according to stewardship, in particular.Among these, given that the steward’s most specific responsibility in planning is to assure stewardship, a sound capacity building is needed as a cornerstone in evolving the culture of the NHS. Furthermore, in order to put this effectively into practice, the Steward must be able to measure S functions, and putting in practice a S model needs international comparison and cultural growth....